Photon versus carbon ion irradiation: immunomodulatory effects exerted on murine tumor cell lines - Hartmann, Laura; Schröter, Philipp; Osen, Wolfram; Baumann, Daniel; Offringa, Rienk; Moustafa, Mahmoud; Will, Rainer D.; Debus, Jürgen; Brons, Stephan; Rieken, Stefan; Eichmüller, Stefan B. (Scientific reports, 2020)
While for photon radiation hypofractionation has been reported to induce enhanced immunomodulatory effects, little is known about the immunomodulatory potential of carbon ion radiotherapy (CIRT). We thus compared the radio-immunogenic effects of photon and carbon ion irradiation on two murine cancer cell lines of different tumor entities. We first calculated the biological equivalent doses of carbon ions corresponding to photon doses of 1, 3, 5, and 10 Gy of the murine breast cancer cell line EO771 and the OVA-expressing pancreatic cancer cell line PDA30364/OVA by clonogenic survival assays. We compared the potential of photon and carbon ion radiation to induce cell cycle arrest, altered surface expression of immunomodulatory molecules and changes in the susceptibility of cancer cells to cytotoxic T cell (CTL) mediated killing. Irradiation induced a dose-dependent G2/M arrest in both cell lines irrespective from the irradiation source applied. Likewise, surface expression of the immunomodulatory molecules PD-L1, CD73, H2-Db and H2-Kb was increased in a dose-dependent manner. Both radiation modalities enhanced the susceptibility of tumor cells to CTL lysis, which was more pronounced in EO771/Luci/OVA cells than in PDA30364/OVA cells. Overall, compared to photon radiation, the effects of carbon ion radiation appeared to be enhanced at higher dose range for EO771 cells and extenuated at lower dose range for PDA30364/OVA cells. Our data show for the first time that equivalent doses of carbon ion and photon irradiation exert similar immunomodulating effects on the cell lines of both tumor entities, highlighted by an enhanced susceptibility to CTL mediated cytolysis in vitro.